Pengembangan Bahan Ajar IPA Berbasis Media Komik di Kelas III SDN Doyong 2 Kota Tangerang - Cahyani, Khoerotus Dita Ayu Puji; Zuliani, Rizki; Wibisana, Ns. Elang (ALSYS, 2021)
The purpose of this research is to develop comic media-based teaching materials for students of grade III SDN Doyong 2 Tangerang City that are worthy of use in IPA subjects of Material Change of Objects. The development of this teaching material follows the addie model development procedure that has 5 stages, namely: analysis, design, development, implementation, evaluate. The results showed that the assessment of media experts, material experts, educators, as well as individual trials, small group trials, and large group trials involving 27 students of SDN Doyong 2 Tangerang City. Data analysis techniques using qualitative and quantitative. The media expert's ratings point to excellent categories with an average score of 4.5. Expert assessment of the material showed a good category with an average score of 3.7. Expert assessment of educators showed excellent categories with an average score of 4.5. Then individual trial data with a score of 4.3 then belongs to the category of very good. The results of the small group test with a score of 4.4 then fall into the category of excellent. The results of large group / field trials with an average score of 4.6 then fall into the category of very good. Thus it can be concluded that IPA teaching materials based on comic media are worth using in IPA learning activities of object change material in SDN Doyong 2 Tangerang City.